2017
DOI: 10.3892/or.2017.5508
|View full text |Cite
|
Sign up to set email alerts
|

BAMBI overexpression together with β-sitosterol ameliorates NSCLC via inhibiting autophagy and inactivating TGF-β/Smad2/3 pathway

Abstract: Abstract. Non-small cell lung cancer (NSCLC) has the highest mortality rate among all solid tumors with a poor prognosis. The BMP and activin receptor membrane bound inhibitor (BAMBI) has been identified as a hallmark of NSCLC and β-sitosterol possesses antitumor potentiality. This study explores the effect of BAMBI overexpression and β-sitosterol in the context of NSCLC. The results revealed that the transfection of pcDNA-BAMBI and β-sitosterol treatment significantly reduced the levels of autophagy markers l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…In the present study, it was demonstrated that Ep3 deficiency was involved in the regulation of cell viability, migration, invasion and apoptosis of A549 cells, and the underlying molecular mechanisms were investigated further. A number of studies have reported that TGF-β/Smad signaling is an important pathway in the progression of NSCLC ( 31 – 33 ), therefore whether TGF-β/Smad signaling mediated the roles of Ep3 was further investigated in A549 cells. The expression of pathway-associated proteins was evaluated using western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, it was demonstrated that Ep3 deficiency was involved in the regulation of cell viability, migration, invasion and apoptosis of A549 cells, and the underlying molecular mechanisms were investigated further. A number of studies have reported that TGF-β/Smad signaling is an important pathway in the progression of NSCLC ( 31 – 33 ), therefore whether TGF-β/Smad signaling mediated the roles of Ep3 was further investigated in A549 cells. The expression of pathway-associated proteins was evaluated using western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Beta-sitosterol (β-sitosterol) induced G0/G1 cell cycle arrest and inhibited cell proliferation in A549 cells. These results indicate that beta-sitosterol may serve as novel targets for the treatment of NSCLC [40]. Bio-assay guided fractionation showed the presence of phytosteols (β-sitosterol) which significantly inhibited the growth of A549 cells and promoted apoptosis alone or in combination.…”
Section: Constructing the Network Of Herb-ingredient-target-lc Therapmentioning
confidence: 77%
“…Beta-sitosterol, a phytosterol induces anticancer properties in different cancers based on different mechanisms [38]. It is indicated that beta-sitosterol induced G0/G1 cell cycle arrest in NSCLC cells possibly by inactivating the TGF-β/Smad2/3/c-Myc pathway [39]. Beta-Sitosterol which has been shown to have reverse MDR on leukemia via induces G2/M arrest, endoreduplication, and apoptosis through the Bcl-2 and PI3K/Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%